A new member of the AKH/RPCH family that stimulates locomotory activity in the firebug, Pyrrhocoris apterus (Heteroptera) - Kodrík, D; Socha, R; Simek, P; Zemek, R; Goldsworthy, G J (Insect biochemistry and molecular biology, 2000)
A new member of the AKH/RPCH family was isolated and identified from the corpora cardiaca of the firebug Pyrrhocoris apterus. The peptide was isolated in a single step by reversed phase HPLC and the structure deduced from the multiple MS (MS(N)) electrospray mass spectra and amino acid analysis as that of an octapeptide with the sequence pGlu-Leu-Asn-Phe-Thr-Pro-Asn-Trp-NH(2): this sequence was confirmed by synthesis. The synthetic peptide induced lipid mobilisation and stimulated locomotory activity in macropterous females. This peptide, designated as Pyrrhocoris apterus adipokinetic hormone (Pya-AKH), is the first identified adipokinetic hormone described in a representative species of the suborder Heteroptera.
Keywords: Insect Hormones; Oligopeptides; Motor Activity; kyselina pyrrolidonkarboxylová; hmyzí hormony; Pyrrolidonecarboxylic Acid; Animals; Neuropeptides; oligopeptidy; Heteroptera; zvířata; pohybová aktivita; neuropeptidy